Sudden Death of an Asymptomatic Patient with Anomaly of the Circumflex Coronary Artery: An Autoptic Case - Andrea, Marzullo; Antonio, d’Amati; Cecilia, Salzillo; Teresa, Lettini; Luciana, Scuccimarri; Egidio, Romano Daniele; Gabriella, Serio (Archives of Clinical and Medical Case Reports, 2022)
Coronary artery anomalies are a rare congenital heart anomaly including a large spectrum of defects. Of all coronary anomalies the anomalous origin of the circumflex artery is relatively common and mostly clinically silent. In some patients, it is diagnosed during angiography performed for chest pain or arrhythmia or acute coronary syndrome. We report an autoptic case with an abnormal circumflex coronary originating from the right coronary artery, in a 60-years-old man submitted to hyaluronic acid injection for gonarthrosis. No other pathologies were referred. The only atherosclerosis factor risk investigated was the cigarette smoking (10-15 cigarettes/die). A subocclusive stenosis (90%) of the origin of the abnormal circumflex and a stenosis of 50% of the anterior descendent artery were detected. According to classification criteria of coronary artery anomalies it is classified as “benign” and considered not able to lead neither myocardial ischemia nor sudden death. Otherwise, our case supports the hypothesis that an anomalous right-angle origin of an artery would favour early atherosclerosis and increase the risk of sudden death also in absence of other relevant risk factors for atherosclerosis.